2012
DOI: 10.1002/jctb.3717
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surfactant on styrene removal from waste gas streams in biotrickling filters

Abstract: BACKGROUND: The performance of two biotrickling filters (BTFs) was evaluated for styrene removal from gas streams at the start-up period and at a pseudo-steady-state under various operating conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 24 publications
2
31
0
1
Order By: Relevance
“…Enhanced removal of hydrophobic VOCs from waste gas by surfactants has also been reported by other investigators. Song et al (2012) report that the RE and EC of a BTF when Triton X-100 was applied were higher than that of the control BTF for treatment of high concentration styrene.…”
Section: Effect Of Organic Lr On N-hexane Removalmentioning
confidence: 94%
See 2 more Smart Citations
“…Enhanced removal of hydrophobic VOCs from waste gas by surfactants has also been reported by other investigators. Song et al (2012) report that the RE and EC of a BTF when Triton X-100 was applied were higher than that of the control BTF for treatment of high concentration styrene.…”
Section: Effect Of Organic Lr On N-hexane Removalmentioning
confidence: 94%
“…Therefore, saponins decreased the growth rate of the microorganisms significantly, and excessive accumulation of biomass within biofilter medium bed could be prevented. Song et al (2012) report that Triton X-100 can also prevent the growth of microorganisms although at a lesser degree, and the pressure drop values for one BTF reached to about 130 Pa on in 70 days, while another BTF only increased to 80 Pa in which Triton X-100 existed. Wang et al (2012) also show that the increase of both the biomass concentration within the media and the pressure drop between the outlet and inlet occurred simultaneously during the whole operation period, which indicates that the pressure drop can be utilized as an index to monitor biomass concentration in packing media.…”
Section: Effect Of Organic Lr On N-hexane Removalmentioning
confidence: 95%
See 1 more Smart Citation
“…Song et al used a nonionic surfactant to improve the removal efficiency of styrene at high organic loading rates in BTFs. The results showed that at an average organic loading rate of 201.7 g m ‐3 h ‐1 , the removal efficiency of styrene increased from 50% in the absence of surfactant to 82% in the presence of surfactant . To enhance the bioavailability of n‐hexane in biofilters, Cheng et al examined the effect of addition of an anionic surfactant in the feeding nutrient solution of BTFs.…”
Section: Resultsmentioning
confidence: 99%
“…Many researchers have studied the use of synthetic surfactants to enhance the RE of biofiltration. Tomadol 25-7 and saponins for n-hexane, 33,34 Tween 20 for toluene, 35 and Triton X-100 for styrene 36 were used for improving degradation in the fungi biofilter. However, the authors believe that the use of a biosurfactant such as Surfactin in a biofilter system has not been reported in the literature.…”
mentioning
confidence: 99%